Efficiency and effectiveness of hotels in Kuala Lumpur and factors affecting their performance - Rahmati, Elham (2015)
The hotel industry in Malaysia receives about 31 percent of tourists’ travel expenditures. This industry highly contributes to the revenue of the tourism industry as the second largest foreign exchange earner in Malaysia. However, it has been performing inefficiently due to under capacity utilization during the last few years. This under capacity utilization of the hotels as well as the low level of Malaysian room rates compared to the room rates in the Asia Pacific region, affect the performance of the hotels adversely. Therefore, the hoteliers should promote efficiency to remain competitive in the market. Due to the perishable nature of the hotel services, all what is produced may not be sold in practice. It means production and consumption of the hotel services cannot be assumed to be the same. Hence, to consider the not-utilized portion of production in the performance analysis, a joint measurement of service production efficiency and service consumption effectiveness should be applied to fully capture the overall performance. Accordingly, this study employs a two-stage DEA model to identify the main sources of inefficiency of the hotels in Kuala Lumpur from 2004 to 2010. Based on the results, none of the hotels of interest operates at the maximum productivity level; therefore, the inefficiency of the hotels is due to either technical problems or operational scale problems or both. The findings show that the dominant source of inefficiency in three- to five-star hotels in Kuala Lumpur stems from technical problems in the sales process. That is to say, the hotels; particularly those of higher star-ranking have more managerial problems in transforming the service capacity into the revenue. The inefficiency of the hotels is further intensified by outweighing the loss of the competition over the agglomeration benefits in the hotel clusters in Kuala Lumpur. However, operating in smaller size in terms of room supply, operating as a chain hotel, being quoted on the stock market, and having foreign shares in the hotel capital improve the efficiency of the hotels. Moreover, based on the marketing performance analysis, the hotels especially the higher star-ranking ones tend to have more technical problems in transforming the marketing inputs into the occupied rooms. The hotels particularly the lower starranking ones have more managerial problems in transforming the occupied rooms into the profit. According to the results, on average, the marketing effectiveness of the hotels during the period under study is 29 percent. It implies that the maximum profit made using the capacity of the hotels is about 29 percent of the maximum profit that could be made using the same service capacity and marketing technology on the overall frontier. There is also a highly positive correlation between marketing efficiency and marketing effectiveness. That is, improving marketing efficiency would lead to higher profitability level.